Influence of the stationary and mobile phase composition in ideal chromatographic systems on the log k values in column chromatography. I. ODS/methanolwater system - G. VUCKOVIC; M. B. CELAP; T. J. JANJIC (Journal of the Serbian Chemical Society, 2000)
On the basis of the literature data it was established that in the case of ODS column chromatography with methanol as modifier the value log xS/x1 (where xS and x1 denote methanol mole fractions in the stationary and the mobile phase, respecitvely) is a linear function of the corresponding Boschs PMN parameter as well as of the log k value of the investigated substances. It was also found that the phase equilibrium in the system ODS/methanol-water is in accordance with the Everetts equation for ideal systems (K = 10.88). Finally, a linear relationship between the log xS/x1 values and the volume fraction of methanol (j) was found in the range of 0.51.0, which corresponds to the linear part of the function log k = f(j), established experimentally by other authors.